Analysis of Downstream Entrepreneurs' Knowledge in South Sumatera Forestry Agribusiness: Impact on Certified Raw Material Selection - Anna Ilmika; Muhammad Yamin; Sabaruddin Kadir (Jurnal Penelitian Pendidikan IPA, 2023)
The wood industry is a downstream forestry sector. So, as an industry that uses wood as the main raw material, this industry is very dependent on the forestry sector. The relationship between the timber and forest industries is very close, and these two sectors influence each other. Analyzing the relationship between the level of knowledge of entrepreneurs regarding the sustainability of wood raw materials and the decision to buy certified wood or not is something that is really needed to become the basis for sustainability. By using a mixed-method research method, it is hoped that this research will be able to contribute to describing the situation of knock-down house entrepreneurs so that they can have a positive impact on the South Sumatra forestry agribusiness system. This research found that the level of knowledge of knock-down house entrepreneurs about certified wood is very low. It was detected that only 3.5% of entrepreneurs used certified wood. Meanwhile, almost 70% of respondents stated that they were not very interested in knowing more about certified wood. This situation is known to have a very significant level of influence on preferences for selecting certified raw materials or not. Â